Crinipellis graminea sp. nov. (Marasmiaceae), a novel taxon from Hasilpur forest, southern Punjab, Pakistan - Asif, Muhammad; Saba, Malka; Akram, Wajahat; Maula, Fazli; Ullah, Fahim; Raza, Mubashar (Phytotaxa, 2025)
Crinipellis graminea is described as a new fungal species from the Hasilpur Forest, southern Punjab, Pakistan. The species is distinctively characterized by its pulvinate to plano-convex pileus with an orange center and a radially fibrillose to wrinkled surface, rarely obovoid basidiospores (3.4–7 × 2–3.8 µm), narrowly clavate to narrowly lageniform cheilocystidia, and elongate clavate pleurocystidia with pointed tips. Molecular analyses involved sequencing both ITS and 28S rDNA regions, with phylogenetic trees constructed using maximum likelihood and Bayesian inference methods. These analyses confirmed that C. graminea forms a distinct clade. The integration of morpho-anatomical and molecular data robustly supports its taxonomic status as a new species. This study advocates for continued exploration and documentation of fungal species in this underrepresented region, essential for a more comprehensive understanding of regional and global fungal diversity.